Women's leadership learning: A reflexive review of representations and leadership teaching. Issue 4 (September 2013) - Stead, Valerie; Elliott, Carole
This article contributes to understandings of the experiential nature of leadership learning by drawing attention to the role of disruption as an organizing influence on women's leadership learning, and by generating insights for leadership teaching. Examining leadership learning as an experiential process, we present the development of a typology intended to act as a summary of literature focusing on women's experiences of leadership learning. Informed by our experiences of developing and using the typology as a teaching aid in two leadership development interventions we progress through a cycle of critical reflections to present a reflexive analysis of the typology's performative effect and how it brings into being representations of women's leadership. Moving from initial observations to deeper reflections the analysis draws attention to how disrupting pervades women's learning of leadership, thus extending our understanding of gender's influence on organizing learning experiences. The article considers how we, as educators, might forefront disrupting as a process in leadership learning interventions by re-positioning instruments, such as the typology, to problematize and deconstruct leadership learning. We conclude by proposing a reflexive process in the classroom that takes the form of a critical dialogue to enable educators and participants to de-construct their experience.